Unraveling the interplay between sleep, redox metabolism, and aging: implications for brain health and longevity - Mir, Fayaz A.; Lark, Arianna R. S.; Nehs, Christa J. (Frontiers in Aging, 2025)
The relationship between sleep and metabolism has emerged as a critical factor in aging and age-related diseases, including Alzheimer’s disease and dementia. Mitochondrial oxidative phosphorylation, essential for neuronal energy production, also generates reactive oxygen species (ROS), which increase with age and contribute to oxidative stress. Sleep plays a vital role in modulating redox balance, facilitating the clearance of free radicals, and supporting mitochondrial function. Disruptions in sleep are closely linked to redox imbalances, and emerging evidence suggests that pharmacological interventions, such as dual orexin receptor antagonists and antioxidant-based therapies, may help restore redox homeostasis. Furthermore, antioxidant-rich diets and supplements have shown promise in improving both sleep quality and metabolic health in aging populations. Neurons, with their high energy demands, are particularly vulnerable to oxidative damage, making redox regulation crucial in maintaining brain integrity. This review explores the bidirectional relationship between sleep and redox metabolism through five key areas: (1) sleep’s role in free radical regulation, (2) ROS as mediators of age-related sleep disturbances, (3) feedback loops between impaired sleep and brain metabolism, (4) sleep, redox, and aging in peripheral systems, and (5) therapeutic strategies to restore redox balance and improve aging outcomes. Understanding these mechanisms may provide new targets for interventions aimed at mitigating age-associated diseases.